Case report: a precancerous lesion associated with HPV in the anal canal diagnosed by magnifying endoscopy with narrow-band imaging and resected by endoscopic submucosal dissection - Li, Hengcun; Sun, Xiujing; Yang, Ling; Xu, Rui; Li, Peng (Frontiers in Medicine, 2023)
Although anal caner remains rarely diagnosed in the world, its frequency is rising, especially in high-risk groups. The prognosis of advanced anal cancer is poor. However, there are still few reports on the endoscopic diagnosis and treatment of early anal cancer and its precancerous lesions. A 60-year-old woman was referred to our hospital for endoscopic treatment of a flat precancerous lesion in the anal canal, which was identified by narrow band imaging (NBI) and confirmed by pathological examination in another hospital. The pathological results showed high-grade squamous intraepithelial lesion (HSIL) in the biopsy specimen, and immunochemistry staining showed P16 positive, suggesting HPV infection. We performed pre-resection endoscopic examination for the patient. A lesion with clear margin and tortuous dilated vessels was revealed under magnifying endoscopy with NBI (ME-NBI), which stayed unstained after iodine spraying. The lesion was successfully removed en bloc using ESD without complications, and the resected specimen was low-grade squamous intraepithelial lesion (LSIL) with positive immunochemistry staining of P16. The patient went follow-up coloscopy a year after ESD, and the anal canal healed well with no suspicious lesions found. From this case, we can learn that ESD is safe and effective for a curative resection of precancerous lesions of anal canal.